THE POLITICAL ECONOMY OF GWADAR PORT DEVELOPMENT: A PERCEPTION FROM LOCAL COMMUNITY - Ahmed, Dr. Manzoor; Kamal, Ms. Latifa; Qayoom, Mr. Abdul (Hanken, 2014)
For the port development the resources of local community are used as the greater economic and social benefits that port is likely to generate payoff to local community in turn in the shape of job creation, logistics infrastructure and overall regional economic and social development. Therefore, the port may be developed considering the economic and social interest of the local community. Gwadar port was developed in 2001 amid great controversy, mainly because of its negative fallout to the livelihood of local community. The aim of the paper was to determine how local community belonging to different demographic and income groups realized the importance of the development of port to their overall economic and social benefits. We composed a sample of 200 respondents who were involved either in the outcomes of the port activities or affected by the port development and operation. Our results revealed that people of Gwadar had great concern to the overall impact of the port development to socio-economic situation of Gwadar. Results further showed that due to the overwhelming presence of China, the local people suspected that Gwadar port has been built not as a economic and commercial port to boost the local and regional economy, but on the contrary it was covertly meant to be a strategic outpost that could be used as part of the Chinese neo-liberal expansionist policies. Given the geo-strategic location of Gwadar it is pertinent to maintain that the growing Chinese is beyond the economic and commercial ones. Instead the question of Gwadar port being used for strategic purpose is an imminent perception. Gwadar port caused a great deal to the local fishing industry, livelihood of the fishermen, and their sociology and economics. Overall our this research showed that people of Gwadar although were not outright opponent to the development of port project, but they had their doubts and suspects on numerous fallout that the port project would expectedly accompany, and that were too detrimental to their local economy, culture, language et al to ignore.